Temporal inequality of nutrient and sediment transport: a decision-making framework for temporal targeting of load reduction goals. (18th December 2020) - Preisendanz, Heather E; Veith, Tamie L; Zhang, Qian; Shortle, James
Abstract: Nutrient and sediment transport exhibit strong spatial and temporal inequality, with a small percentage of locations and events contributing to the vast majority of total annual loads. The processes for determining how to reduce total annual loads at a watershed scale often target spatial, but not temporal, components of inequality. We introduce a framework using Lorenz Inequality and corresponding Gini Coefficient to quantify the temporal inequality of nutrient and sediment transport across the Chesapeake Bay watershed. This long-impaired, 166 000 km 2 watershed has been federally mandated since 2010 to continually reduce nutrient and sediment loads reaching the Bay. Data were obtained for 108 sites in the Chesapeake Bay's non-tidal network from 2010 to 2018. The Lorenz Inequality and Gini Coefficient analyses were conducted using daily-scale data for flow and loads of total nitrogen (TN), total phosphorus (TP), and total suspended sediment (TSS) at each gaging station. We leverage these results to create a 'temporal targeting framework' that identifies periods of time and corresponding flow conditions that must be targeted to achieve desired or mandated load reduction goals across the watershed. Among the 108 sites, the degree of temporal inequality for TP and TSS (0.37–0.98) was much greater than for flow and TN (0.29–0.77), likely due to the importance of overland versus baseflow in the transport pathways of the respective constituents. These findings stress the importance of informed design and implementation of best management practices effective in 'hot moments, ' and not just 'hot spots, ' across impaired watersheds to achieve and maintain water quality restoration goals. The 'temporal targeting framework' detailed in this manuscript provides a useful and convenient method for watershed planners to create low- and high-flow load targeting tables specific to a watershed and constituent.